A study on motivation factors and job performance at system consultancy services company / Nor Safna Simun - Simun, Nor Safna (Faculty of Business and Management, 2007)
This research is conduct to carry out "A Study On Motivation Factors and Job Performance At System Consultancy Services". The main objective is to determine the relationship between motivation factors and job performance. As we know, increasingly competitive business world means a highly motivated workforce is needed for organization seeking to achieve good result performance. In order to achieve that result an employers should learn on how to motivate employees in the company. The respondents of this study were the employee of System Consultancy Services. 50 questionnaires has been distributed them but only 35 give respond. The researcher had been used probability sampling as a sampling technique.